Techniczne „rozszerzenia” ciała i wartość ciała ludzkiego - Gruchoła, Małgorzata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2019)
The aim of the article was to present the influence of changes to the body-machine system, resulting from the application of innovative technologies and the strategy of cyborgization on the perception of and assignment of value to the human body in contemporary society. I apply two research approaches. On the one hand, the non-invasive functioning of the body-machine system as an expression of transgression; on the other one: the functioning of a machine connected with a body (exo-extension), the functioning of a machine in a body (endo-extension) and the functioning of a body in a machine (mind uploading), as an expression of transhumanism. Addressing the problem formulated in the title of this article, I postulated the hypothesis that undermining the natural status of the human body in postbiological society, favoured by cyborgization and the application of innovative technologies, resulting from a controlled social discourse and knowledge, changing the body-machine relations, changes the perception of and assignment of value to the human body. The hypothesis was confirmed. The article is analytical and descriptive. The research problem is analysed from the sociological perspective.